Reduction chemistry-assisted nanopore determination method for immunoglobulin isotypes. Issue 38 (23rd September 2020) - Liu, Qianshan; Wang, Yunjiao; Liu, Yaqing; Wang, Han; Li, Wei; Tang, Peng; Weng, Ting; Zhou, Shuo; Liang, Liyuan; Yuan, Jiahu; Wang, Deqiang; Wang, Liang
Abstract : A reduction chemistry-based, molecular dynamics simulation-assisted nanopore method was developed for the simultaneous determination of IgG and IgM without any concerns of undesirable effects to blood. Abstract : Immunoglobulins can bind to an unlimited array of foreign antigens presented to the immune system. Among those isotypes, IgG and IgM play crucial roles in initial immune defense associated with innate immunity factors. Hence, the determination of IgG and IgM deficiencies or varying concentrations is widely used as a diagnostic indicator for immune deficiency disorders. Herein, we report a reduction chemistry-assisted nanopore method for IgG and IgM determination. TCEP (tris(2-carboxyethyl)phosphine) was used to cleave Ig proteins in fragments by means of disulfide bond reduction under different experimental conditions. This strategy enabled the observation of distinguishable current signals afforded by separated polypeptide fragments in an αHL nanopore. Together with molecular dynamics (MD) simulation results, highly effective electrostatic potentials and H-bonds, the dominant factors for these current signals, facilitated the capture of Ig fragments in an α-HL nanopore. More importantly, the signature signals were applicable for differentiating between IgG and IgM in blood serum without any problems of protein adsorption and clogging in the nanopore sensing. Furthermore, with comparative sensing sensitivity and selectivity, it is concluded that our method is a label-free single-molecule approach to measuring disease states that present as a result of the absence or over presence of immunoglobulin isotypes.